Neoadjuvant/adjuvant treatment of high-risk retinoblastoma: a report from the German Retinoblastoma Referral Centre. Issue 7 (12th January 2015) - Künkele, Annette; Wilm, Josephine; Holdt, Markus; Lohmann, Dietmar; Bornfeld, Norbert; Eggert, Angelika; Temming, Petra; Schulte, Johannes H
Abstract : Background: Retinoblastoma can extend beyond the structures of the eye, where cells can enter the bloodstream and cause metastases. Various types of protocols for adjuvant treatment risk-adapted according to histopathological risk factors are used worldwide. Methods: Between 1997 and 2009, 420 children were diagnosed with retinoblastoma at the German Retinoblastoma Referral Centre and risk factors were assessed. Patients with post-laminar optic nerve infiltration or choroid or minor scleral invasion received six courses of adjuvant chemotherapy using vincristine, etoposide, carboplatin and cyclophosphamide (group 1). Patients with microscopic extension beyond the sclera to the resection margin of the optic nerve or potential spread due to vitrectomy received chemotherapy plus orbital radiotherapy (group 2). Neoadjuvant chemotherapy was performed in patients with local extraocular invasion detected on MRI. Results: Following this protocol, 42 of the 420 patients and 21 referred from other centres showed high-risk histopathological factors qualifying for adjuvant therapy (57 in group 1 and 6 in group 2). Seven of the 63 patients received neoadjuvant and adjuvant treatment. During a mean follow-up of 5.8 (range 0.4–15.4) years, one of six patients in group 2 developed metastases and died. No patients died from toxicity. The 5-year overall survival was 100% for group 1 and 80% for group 2. Conclusions: This retrospective single-site study reveals a 10% incidence of high-risk features in children with retinoblastoma diagnosed at the German Retinoblastoma Referral Centre. Overall survival rates of 98.3% underline the safety of this adjuvant chemotherapy protocol and its efficiency in preventing metastasis.